Peculiarities of Lymph Fluid and Its Rheology as a Metastasisin - A. V. Sultanbaev; K. Sh. Gantsev; Sh. R. Kzyrgalin; N. M. Mansurovich (Креативная хирургия и онкология, 2019)
Introduction. Despite the large number of scientific studies on metastasis problems, the state of liquid media (lymph and blood) in oncological diseases remained without sufficient attention.Materials and methods. A study of the lymph fluid properties, including viscosity, of 100 female patients with malignant breast tumours was carried out. The age of the patients ranged from 50 to 80 years. All patients were in menopause. The material for determination of viscosity was taken 5–7 days following mastectomy with extended dissection of axillary lymph nodes. On the first and second days, the contents of the wound were represented by blood clots and serous fluid. Between three- and five-days following surgery, the discharge from the wound consisted of serous discharge, prelims and lymph. On the fifth day and the following days, the wound discharge consisted primarily of lymph fluid caused by the completed haemostasis and continuation of discharge from the small lymphatic vessels.Results. The metastatic process is more active during the initial stages of cancer, since the metastatic medium is represented by less viscous lymph fluid while the vessels for the most part retain their permeability. With advanced stages of cancer, when the viscosity of the lymph rises, metastasis slows down.Conclusions: (1) In breast cancer, the viscosity depends on the stage of the cancer, while the lymph in the tumour pool behaves like a non-Newtonian fluid. (2) In stages I-II of cancer, metastasis occurs more actively than in cancer at more advanced stages. This phenomenon is determined by the rheological properties of the lymph and the functional viability of the regional vascular system.